Komunikasi Visual untuk Kampanye Gerakan 3R (Reduce-Reuce-Recycle) di Bandung - Homan, Devi Kurniawati (Bina Nusantara University, 2013)
Bandung, which known as Flower City and Paris van Java, is a city tourism destination for domestic tourists and international tourists. Bandung becomes shopping and culinary travel destination. The consumption for plastic and garbage increases by the increase of tourists. Bandung suffers for garbage problem. To prevent it happens again to Bandung, it needs a campaign for garbage problem solution. It only takes three steps for decrease the garbage problem. The three steps are ‘Reduce, Reuse, Recycle’. Tourists can help to keep clean and comfort for Bandung environment. The campaign itself can be accessed in internet with smartphone, which is common for young generation. Information can easily spread and hope it becomes a good habit for Bandung tourists.